Kakothrips acanthus Berzosa (Thysanoptera: Thripidae) in Türkiye, with an illustrated key to the species of Kakothrips - Negi̇ş İnci̇ Şahi̇n (Zootaxa, 2023)
Kakothrips acanthus Berzosa, previously known only from Spain and Sicily, is newly reported from Türkiye, based on a single female. Diagnostic characters of the specimen are provided, also an illustrated key to the eight species of Kakothrips Williams, and available data on the plant associations of these species. Females of Kakothrips priesneri are considered remarkable among Thripinae in having sternal pore plates.